Tobacco Cessation Practices and Attitudes Among Nurses in the Czech Republic - Sarna, Linda P; Bialous, Stella Aguinaga; Králíková, Eva; Kmetova, Alexandra; Felbrová, Vladislava; Kulovaná, Stanislava; Malá, Katerina; Roubíčková, Eva; Wells, Marjorie J; Brook, Jenny K (Cancer nursing, 2015)
BACKGROUND: Tobacco is the leading cause of cancer in the Czech Republic. More than one-third of the population older than 15 years smokes, including many nurses. Most smokers want to quit, but the extent of nurses' involvement in tobacco cessation is unknown. OBJECTIVE: The purposes of this study are to describe the frequency of nurses' interventions in helping smokers quit, examine their attitudes and skills, and explore the relationship of nurses' smoking status to level of intervention. METHODS: A convenience sample of nurses in the Czech Republic completed a survey about their frequency of interventions according to the 5As for tobacco dependence treatment (i.e., ask, advise, assess, assist, arrange), their attitudes and perceived skills, and their smoking status (never, former, current). RESULTS: A total of 157 nurses completed the survey; 26% "always" or "usually" assisted patients with smoking cessation. Few (22%) reported that nurses could play an important role in helping patients quit, and 65% rated their ability to help smokers quit as "fair/poor." Nurse who smoked (30%) were less likely to consistently assess smoking status or arrange for follow-up support. CONCLUSION: Few nurses in the Czech Republic consistently provide smoking cessation support to patients, have the skills to do so, or view this role as an important part of their role. IMPLICATIONS FOR PRACTICE: To reduce tobacco-related cancers in the Czech Republic, capacity-building efforts are needed to enhance nurses' skills and confidence in providing smoking cessation interventions. Support is also need to help nurses who smoke quit.
Keywords: vztahy mezi ošetřovatelkou a pacientem; Health Care Surveys; Practice Patterns, Nurses'; Nurse's Role; Humans; Attitude of Health Personnel; Clinical Competence; lidé středního věku; ošetřovatelství - vzorové postupy; Nursing Staff, Hospital; Female; dospělí; personál sesterský nemocniční; prevence kouření; lidé; klinické kompetence; role ošetřovatelky; odvykání kouření; Smoking Cessation; Adult; Social Support; ženské pohlaví; Middle Aged; Czech Republic; Nurse-Patient Relations; průzkumy zdravotní péče; postoj zdravotnického personálu; Smoking; sociální opora; Česká republika; kouření; Smoking Prevention